Fractional Erbium laser in the treatment of photoaging: randomized comparative, clinical and histopathological study of ablative (2940nm) vs. non-ablative (1540nm) methods after 3 months - Juliano Borges; Tullia Cuzzi; Carlos Alberto Mandarim-; Mônica Manela-Azulay (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Fractional non-ablative lasers keep the epidermis intact, while fractional ablative lasers remove it, making them theoretically more effective. OBJECTIVES: To evaluate the clinical and histological alterations induced by fractional photothermolysis for treating photoaging, comparing the possible equivalence of multiple sessions of 1540nm Erbium, to one session of 2940nm Erbium. METHODS: Eighteen patients (mean age 55.9) completed the treatment with three sessions of 1540nm fractional Erbium laser on one side of the face (50 mJ/mB, 15ms, 2 passes), and one session of 2940nm on the other side (5mJ/mB, 0.25ms, 2 passes). Biopsies were performed before and 3 months after treatment. Clinical, histological and morphometric evaluations were carried out. RESULTS: All patients presented clinical improvement with no statistically significant difference (p> 0.05) between the treated sides. Histopathology revealed a new organization of collagen and elastic fibers, accompanied by edema, which was more evident with the 2940nm laser. This finding was confirmed by morphometry, which showed a decrease in collagen density for both treatments, with a statistical significance for the 2940nm laser (p > 0.001). CONCLUSIONS: Three 1540nm sessions were clinically equivalent to one 2940nm session. The edema probably contributed to the positive results after three months, togheter with the new collagen and elastic fibers organization. The greater edema after the 2940nm session indicates that dermal remodeling takes longer than with 1540nm. It is possible that this histological superiority relates to a more prolonged effect, but a cohort longer than three months is needed to confirm that supposition.